INDICATORS OF ANTICOAGULATIVE ACTIVITY OF VASCULAR WALL DEPENDING ON STAGE OF BREAST CANCER - I.L. IVANENKO; S.I. VERETENNIKOV; V.V. NIKITINA; V.V. BLINOVA; E.A. ROGOZHNIKOVA; S.S. VERETENNIKOV (Avicenna Tajik State Medical University, 2017)
Objective: Detection the intensity of changes in the anticoagulant activity of the vascular wall, depending on the stage of breast cancer. Methods: Study of the hemostasis system carried out in 84 women who had medical treatment in the Oncology Department of the Road Clinical Hospital with a diagnosis of breast cancer and received chemotherapy, radiation therapy and surgical treatment in various combinations. The comparison group consisted of 35 women without oncological pathology of the same age. Results: According to the results of the cuff test, the most pronounced inhibition of the ability of the endothelium to produce activators of fibrinolysis, anticoagulants and antiplatelet agents before and after the operation revealed in patients with stage II and III of the tumour process Conclusion: The revealed changes in the anticoagulant activity of the vascular wall indicate an increased risk of thrombogenic complications after surgical intervention in patients with stage II and III breast cancer.